The Role of Sustainability Perception in Consumer Behavior: A Study of Packaging, Ingredients, and Brand Awareness in the Soft Drinks Industry - Jian, Oh Zi; Baliyan, Meenu; Gadi, Paul Dung; Siva-Muniandy, Serena Taherin A/P; Azman, Salma Binti; Mohamad Yusoff, Salsabila Binti; Mohamad Nadzri, Siti Nurhafiza Binti; Bansal, Mani; Kumar, Kuldeep; Srivastav, Kundan Pratap; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
This research seeks to understand howingredients, packaging, brand awareness,and sustainability perception interact andinfluence consumer behavior in the softdrinks industry, specifically Coca-Cola. Theonline survey to 100 respondents wasconducted via Google Form and thecollective data was analyzed by the SPSSsoftware. While the research examined theimpact of ingredients and packaging onconsumer decisions (H1 and H2), no directeffect was found. However, the researchrevealed a strong positive correlationbetween sustainability perception andconsumer behavior (H3, R² = 0.391, beta =0.423). Interestingly, a positive relationshipemerged between packaging andingredient impact on one hand, andsustainability perception on the other (H4,beta = 0.778). Additionally, sustainabilityperception was found to positively influencebrand awareness (H5, beta = 0.548). Thesefindings suggest that consumers prioritizesustainability when making purchasingdecisions in the soft drinks industry, andthat a brand's commitment to sustainablepractices can indirectly influence consumerbehavior through positive sustainabilityperception